2013
DOI: 10.3329/bmrcb.v39i1.15791
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response after treatment in patients with chronic hepatitis C infection - a five year follow up

Abstract: Peginterferon α-2a and ribavirin combination therapy achieves a sustained virological response (SVR) in patients with chronic hepatitis C. Little is know about long-term durability of hepatitis C virusRibonucleic acid (HCV-RNA) negativity in patient treated with pegylated interferon and ribavirin therapy. Aim of this study was to evaluate the durability of virologic response in patients with SVR to anti-viral therapy treated at our centre. A total of 52 patients with chronic hepatitis C virus infection who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…With regard to the clinical relevance of patients with positive OCI, all positive OCI cases were cirrhotic with a significant fibrosis score (F3 or F4) and also abnormal liver function tests, especially raised ALT prior to treatment. These findings were also reported in other studies of Rahman et al and Sood et al, which found a definite percentage of OCI that occurs more often in patients with overt cirrhosis 32,33. Elmasry et al examined the occurrence of OCI in HCV-infected liver transplant recipients who achieved SVR with recent DAAs and found an altered aminotransferase levels in 11% of their patients 34.…”
Section: Discussionsupporting
confidence: 73%
“…With regard to the clinical relevance of patients with positive OCI, all positive OCI cases were cirrhotic with a significant fibrosis score (F3 or F4) and also abnormal liver function tests, especially raised ALT prior to treatment. These findings were also reported in other studies of Rahman et al and Sood et al, which found a definite percentage of OCI that occurs more often in patients with overt cirrhosis 32,33. Elmasry et al examined the occurrence of OCI in HCV-infected liver transplant recipients who achieved SVR with recent DAAs and found an altered aminotransferase levels in 11% of their patients 34.…”
Section: Discussionsupporting
confidence: 73%
“…In adults, durability of SVR 5 years after completing PegIFN treatment has been observed to be >99% [4] and cirrhosis appears to be a risk factor for long-term relapse [5].…”
mentioning
confidence: 99%
“…Rahman et al [ 118 ] have reported that a SVR to current IFN treatment regimens is durable in most patients, but not all and that late relapses can occur during long-term followup. Importantly, they reported that this finding occurs more often in patients with cirrhosis.…”
Section: Clinical Relevancementioning
confidence: 99%